Vallens övervintring i norra Finland - Jamalainen, E. A. (Agricultural and Food Science, 1970)
This discussion, with some additions by way of completion, is based upon a paper read by the author in Sollefteå, Sweden, Aug. 14th 1969, where Norwegian, Swedish and Finnish experts discussed some problems relating to agriculture in North Scandinavia. On the basis of research and experiments carried out at plant breeding institutes, local agricultural experimental stations and the Department of Plant Pathology, it has been possible to establish that extensive damage due to low temperature parasitic fungi is not encountered regularly in South or Central Finland. In certain years, however, Fusarium nivale (Fr.) Ces., Typhula ishikariensis Imai (syn. T. idahoensis Remsb.) and T. incarnata Lasch ex Fr. may appear as a cause of injury, even in the Southern parts of the country. Sclerotinia borealis Bub. & Vleugel occasionally causes losses in Central Finland. In Central and South Finland the Scandinavian varieties of timothy (Phleum pratense), meadow fescue (Festuca pratensis) and meadow grass (Poa pratensis) are, as in corresponding conditions elsewhere in Scandinavia, comparatively resistant to low temperature parasitic fungi. Cocksfoot (Dactylis glomerata) is more susceptible to these fungi than the former grasses, as is perennial rye-grass (Lolium perenne) also in South Finland. Overwintering damage to ley grasses in North Finland. Significant results on the overwintering of ley grasses in North Finland have been obtained at the Arctic Circle Agricultural Experimental Station at Apukka, near Rovaniemi. The director of this station, Dr. A. Isotalo, has during several successive springs carried out visual analyses of the damage caused by low temperature parasitic fungi in ley grass trials, which have been run on both peat bog and mineral soils. Table 1 presents data on the damage by F. nivale, S. borealis and T. ishikariensis to a plant stand of timothy, meadow fescue and cocksfoot, according to visual assessments. The plant stand usually recovers during the growing season, so that the economic losses are less ...